A novel measurement method of bulk/scaled dust permittivity at a microwave frequency band as I/P to accurate scattering computations. Part II - Bashir, Saad Osman; McEwan, N.J (Allerton Press Inc, 2012)
In order to compute the scattering properties of individual sand/dust particles dispersed in air, as in a true sand/dust storm, we need to derive a permittivity value which is representative of sand/dust particle with its layer of water. As a first step in this, we applied Looyenga’s formula to extract the permittivity of the dry sand/dust component from the mixture which is measured. Measured results could be used to estimate electromagnetic wave propagation impairments in communication systems.